Rapid evolution in a plant-pathogen interaction and the consequences for introduced host species - Gilbert, Gregory S; Parker, Ingrid M (Evolutionary applications, 2010)
Plant species introduced into new regions can both leave behind co-evolved pathogens and acquire new ones. Traits important to infection and virulence are subject to rapid evolutionary change in both plant and pathogen. Using Stemphylium solani, a native foliar necrotroph on clovers (Trifolium and Medicago) in California, USA, we explore how plant-fungal interactions may change in an invasion context. After four generations of experimental serial passage through multiple hosts, Stemphylium consistently showed increased infection rates but no consistent change in damage to the host. In a historical opportunity study, we compared infection and virulence across four groups of clover hosts: California natives, European clovers not found in California, and both California and European genotypes of species naturalized in California. There was significant variation among hosts, but no pattern across the four groups. However, in direct comparisons of familiar California genotypes to unfamiliar European genotypes of the same naturalized species, Stemphylium consistently infected familiar hosts more frequently, while causing less damage on them. This pattern is consistent with the hypothesis of adaptive evolution in both the pathogen (ability to infect) and the host (tolerance of infection). Together these results suggest the potential for rapid evolution to alter interactions between plant invaders and their natural enemies.